Distributed Leadership: An Effective Practice when Practiced Effectively - Loretta A Rieser-Danner Ph.D.; Jen Bacon Ph.D.; Lori Vermeulen Ph.D. (Academic Chairpersons Conference Proceedings, 2016)
Building transparent models for the distribution of college-level resources, getting buy-in from department chairs, and implementing models across very different departments.
Keywords: Distributed Leadership; Data-driven Resource Allocation; Shared Governance; Budgetary Decision Making; Sharing Resources